Studi Literatur Efektivitas Penggunaan Berbagai Jenis Pengencer yang Ditambahkan Antioksidan Terhadap Kualitas Semen Kambing (Capra aegagrus hircus) - Zaki A. A. Mubaraq; Nancy D. F. K. Foeh; Cynthia D. Gaina (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Goats are ruminants that have considerable potential. The livestock population data in the province of East Nusa Tenggara (NTT) has continued to increase from 2004 to 2018. The Artificial Insemination (AI) program has a function to improve genetic quality and livestock production. Extender is a mixture of various materials that can maintain the quality of spermatozoa in animal semen. Antioxidants to prevent the emergence of oxidant compounds in excess. The purpose of this literature study was to determine which semen extender has effectiveness in improving the quality of goat semen and the active substance that acts as an antioxidant as one of the substances that can improve the quality of the extender. The process of this literature study is carried out by searching and collecting various kinds of existing literature using Google Scholar, Google Patent, Pubmed then all existing references are compiled with the Mendeley application. Reference sources obtained are scientific journals, scientific articles/publications, e-books and national and international seminar proceedings by searching for